The Cumulative Impact of Recurrent Experiences of Intimate Partner Violence on Emotion Dysregulation: A Longitudinal Investigation - Simpson, Lauren E. (Journal of interpersonal violence, 2025)
Intimate partner violence (IPV) disproportionately affects women and has been linked to a range of negative psychological outcomes, including emotion dysregulation. Although IPV is often recurrent and tends to escalate in severity over time, few studies have examined the potential effects of recurrent experiences of IPV on emotion dysregulation. The current study employed a longitudinal design to examine the cumulative impact of recurrent experiences of IPV on emotion dysregulation. Participants were 491 young adult community women (Mage = 21.74; 61.3% White, 35% African American/Black) who completed self-report measures of IPV and emotion dysregulation every 4 months for 28 months. Multilevel structural equation modeling techniques revealed that, at the within-person level, increases in cumulative IPV were associated with increases in global emotion dysregulation across the 28 months. In particular, the accumulation of IPV experiences over time was associated with increases in difficulties controlling impulsive behaviors when distressed and accessing effective emotion regulation strategies. At the between-person level, greater average cumulative IPV was associated with greater mean levels of global emotion dysregulation, as well as four specific dimensions of emotion dysregulation, including difficulties accepting emotional responses, accessing effective emotion regulation strategies, and both engaging in goal-directed behaviors and controlling impulsive behaviors when distressed. These findings suggest the potential cumulative impact of IPV on both global and more specific dimensions of emotion dysregulation. Results also highlight emotion dysregulation as a potentially important construct to assess and target in interventions for women experiencing recurrent IPV.